2019
DOI: 10.3390/resources8010046
|View full text |Cite
|
Sign up to set email alerts
|

How Spatial Analysis Can Help Enhance Material Stocks and Flows Analysis?

Abstract: Spatial information can be integrated into almost all fields of industrial ecology. Many researchers have shown that spatial proximity affects a variety of behaviors and interactions, and thus matters for materials stocks and flows analysis. However, normal tools or models in industrial ecology based on temporal dependence cannot be simply applied to the case of spatial dependence. This paper proposes a framework integrating material stocks and flows analysis with spatial analysis. We argue that spatial analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Specifically, information on the in-use material stock of wind turbines could provide valuable insights into resource utilization efficiency 15 , encompassing material extraction 16 , usage 17 , and offer projections for future scenarios of wind turbine growth and endof-life management 18 . Furthermore, high-resolution and up-to-date monitoring of material stocks embedded within offshore wind turbines carries significant implications for route planning 19 and recycling potential evaluation 20 during the decommissioning phase of the wind turbine. Yet traditional approaches for assessing offshore wind turbines' in-use stocks are generally time-consuming and incomplete, which results in a low spatial resolution and may be outdated due to the rapid growth of offshore wind turbines 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, information on the in-use material stock of wind turbines could provide valuable insights into resource utilization efficiency 15 , encompassing material extraction 16 , usage 17 , and offer projections for future scenarios of wind turbine growth and endof-life management 18 . Furthermore, high-resolution and up-to-date monitoring of material stocks embedded within offshore wind turbines carries significant implications for route planning 19 and recycling potential evaluation 20 during the decommissioning phase of the wind turbine. Yet traditional approaches for assessing offshore wind turbines' in-use stocks are generally time-consuming and incomplete, which results in a low spatial resolution and may be outdated due to the rapid growth of offshore wind turbines 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recognizing the importance of these interlinkages between resources, externalities, and the territory with the economic process, it is advisable to use the conceptual water-energy-food (WEF) nexus to address inter-related issues at different scales and dimensions in order to perform a quantitative analysis of sustainability with a different approach [6][7][8]. In this sense, natural infrastructure (soil, aquatic, and terrestrial ecosystems, atmosphere as ecological resources) or ecological funds (EFs) have been recognized as key components for achieving the 2030 Sustainable Development Goals (SDGs).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Dai et al [29] reported 70 tools and methods that can be used to assess the water-energy (WE) nexus at multiple levels, which includes the performance of a life cycle assessment (LCA) through their standards-ISO-14040, 2006 and ISO-14044, 2006-and other emerging approaches like the multi-scale integrated assessment of society and ecosystem metabolism (MuSIASEM) [8,11,30].…”
Section: Introductionmentioning
confidence: 99%